“Cocinar para mi familia y para la fábrica”: roles de género en la experiencia dekasegi - Silva Zárate, Isaí (2023)
Several decades have passed since the massive migration of Peruvians to Japan. Although the «return home» of many migrants was –and continues to be– heterogeneous and dynamic, little has been explored about the experiences of dekasegi women in a world where the female role is increasingly questioned. Furthermore, it is relevant to give voice to these stories for two main reasons. First, women’s stories are systematically rejected. Second, in a globalized world where identities are increasingly diverse and changing, women’s roles are also being currently questioned. This brought with it new experiences in all fields of life for these women, from work to private life at home. Taking this into account, this paper wants to explore the tensions between work and gender roles, specifically those of maternity and care. These topics are presented based on an interview with a mother who traveled to Kanagawa (Japan) as a dekasegi in the 2000s. Based on her story, it was possible to have a clearer vision of what life was like for these working women and to delve into ideas presented in theory regarding migrants and gender roles with a real example.